2020
DOI: 10.1155/2020/3617514
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Inhibits MDA‐MB‐231 Cells by Attenuating Their Inflammatory Responses

Abstract: Breast cancer initiation is closely associated with cytokines that can change the inflammatory tumor microenvironment. Compounds extracted from plants have been explored for the possibility of cancer treatment in the recent decades. Berberine is an isoquinoline plant alkaloid with remarkable antioxidant and anti-inflammation roles, which is used in ethnic medicines, including traditional Chinese and North American medicine. In the present study, we investigated the effects of berberine on the malignant tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…Zhao and Zhang recently investigated the role of berberine regarding the behavior of the MDA-MB-231 malignant breast tumor cell line. Namely, BBR reduced cell migration ability, provoked inhibition of phosphorylation, decreased overexpression of the tumor necrosis factor α (TNF-α) and Interleukin 6 (IL-6), and induced suppression of the nuclear factor kappa light chain enhancer of activated β cells (NF-Κβ) [ 47 ].…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…Zhao and Zhang recently investigated the role of berberine regarding the behavior of the MDA-MB-231 malignant breast tumor cell line. Namely, BBR reduced cell migration ability, provoked inhibition of phosphorylation, decreased overexpression of the tumor necrosis factor α (TNF-α) and Interleukin 6 (IL-6), and induced suppression of the nuclear factor kappa light chain enhancer of activated β cells (NF-Κβ) [ 47 ].…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…Downregulation of key lipogenic enzymes, leading to suppression of lipid synthesis, which is linked to cell proliferation through the Wnt/β-catenin pathway, has been described as one of the anticancer mechanisms of berberine [ 53 ]. Similarly, the influence on JNK kinases described above is important in anticancer and chemopreventive activity based on the influence on lipid metabolism [ 94 , 95 ].…”
Section: Anticancer Activity Of Berberinementioning
confidence: 99%
“…This finding can be related to the electrostatic interactions occurring between HA and berberine, which made HA less available for promoting cell gap disclosure. Indeed, Zhao and coworkers demonstrated that berberine retarded wound healing in vitro of scratched breast cancer cells [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding can be related to the electrostatic interactions occurring between HA and berberine, which made HA less available for promoting cell gap disclosure. Indeed, Zhao and coworkers demonstrated that berberine retarded wound healing in vitro of scratched breast cancer cells [49]. Finally, the wound-closure-promoting properties of the developed nanogels (NG6B, NG6L) were studied using an in vitro wound-healing assay to preliminarily assess the potentiality of the formulated nanogels for wound-healing applications.…”
Section: Nanogels Characterizationmentioning
confidence: 99%